Knockdown of SIRT1 inhibits proliferation and promotes apoptosis of paclitaxel-resistant human cervical cancer cells - Xia, Xiaoyan; Zhou, Xiaoming (Cellular and Molecular Biology, 2018)
Cervical cancer (CC), a common gynecological cancer, is a primary cause of cancer-related death in women, worldwide. This study investigates the role of Sirtuin 1 (SIRT1) in paclitaxel (PTX)-resistant CC lines. We used qPCR and Western blots to measure SIRT1 mRNA and protein expressions in 10 matched clinical cancer tissues. We compared the expression levels of SIRT1 between sensitive CC cell lines and PTX-resistant cell lines. Subsequently, we used SIRT1 siRNA to knockdown the expression of SIRT1, and then measured cell proliferation, cell apoptosis rate, cell cycle distribution, and expression levels of Bcl-2 and Bax in PTX-sensitive Hela cell line, PTX-resistant Hela and Sila-resistant cell lines. Finally, we detected the location and expression of MRP (multidrug resistance-associated proteins) using immunofluorescence. We found that SIRT1 expression was higher in PTX-sensitive CC tissues than in normal tissues, and significantly higher in PTX-resistant CC tissues than in PTX-sensitive CC tissues. We further demonstrated that knockdown of SIRT1 in PTX-resistant CC cell lines and PTX-sensitive CC cell line inhibited cell proliferation and promoted cell apoptosis. In addition, we observed that blocking SIRT1 expression in PTX-resistant CC cell lines significantly decreased MRP expression. SIRT1 exhibited high expression levels in both PTX-resistant cell lines and patients. Our results suggest that SIRT1 serves as a potential therapeutic target in PTX-resistant CC.